Peran Media Sosial Dalam Demokrasi Masa Kini - Nuraeni Nuraeni; Lupki Lupki; Muhamad Jafar (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Technological developments have penetrated human life. One of the social media that originally only functioned as a means of self-existence, is now changing to influence the political climate of a country. In the democation of the media including the fourth pillar because it is considered more neutral and independent than the elements of state power. With the existence of this social media, the community is increasingly appreciative and active regarding actual issues that occur, of course this can increase public participation related to public issues. This research illustrates that democracy in the digital era can facilitate the process of democracy and social media can be used as a public space to aspire to democracy that is implemented according to the wishes of the people or still needs to be improved, but we as users must be able to choose information so that they do not easily believe in the news hoax. This study uses a survey method with non-physical student subjects at the STISIP Banten Raya.